2021
DOI: 10.1186/s12904-021-00782-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the economic value of end-of-life and palliative care interventions: a narrative review of reviews

Abstract: Background As the demand for palliative care increases, more information is needed on how efficient different types of palliative care models are for providing care to dying patients and their caregivers. Evidence on the economic value of treatments and interventions is key to informing resource allocation and ultimately improving the quality and efficiency of healthcare delivery. We assessed the available evidence on the economic value of palliative and end-of-life care interventions across va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…Our data support the ongoing need for inpatient specialist palliative care services in both acute and elective oncology settings with such a high proportion of cancer patients spending significant amounts of time in hospital in the last year and months of life. We have previously demonstrated that most evidence on the cost-effectiveness of palliative and end-of-life care interventions is related to home-based interventions, with associated substantial reductions in total healthcare costs, resource use and improvement in patient outcomes [ 44 ]. Considering these new data in light of this study, our data provide support for investment in home-based palliative and end-of-life care, which together with appropriate social care, might offer dual benefits of improving outcomes and experiences for patients, and at reduced system costs.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the ongoing need for inpatient specialist palliative care services in both acute and elective oncology settings with such a high proportion of cancer patients spending significant amounts of time in hospital in the last year and months of life. We have previously demonstrated that most evidence on the cost-effectiveness of palliative and end-of-life care interventions is related to home-based interventions, with associated substantial reductions in total healthcare costs, resource use and improvement in patient outcomes [ 44 ]. Considering these new data in light of this study, our data provide support for investment in home-based palliative and end-of-life care, which together with appropriate social care, might offer dual benefits of improving outcomes and experiences for patients, and at reduced system costs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, quality end-of-life specialized care had been found to lower cost because of a decrease in the number of admissions, length of hospital stay, a reduction in the number of ICU stays and emergency hospital visits and the cost during last hospital admission. 7,21,22,30,31 Increasingly, patients in the last of life with multiple or complex diseases have palliative needs. This patient profile is usually admitted to units with high scientific and technical levels, but with a lack of training in palliative care 32 , which may lead to a use of resources that provide no benefits and incur high costs for the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…38 The savings achieved by PC teams during hospital admission are well known. 7,21,31 However, they refer to the cancer population, and focus on reducing hospital stays, days in the ICU, or use of chemotherapy. 39,40 This study included both oncological and non-oncological patients, focusing on the last hospital admission of patients dying in the hospital, showing that savings with PC teams were due to the more appropriate use of hospital resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to evaluate cost-effectiveness, not least because of the lack of clarity about outcome measures. 61 One example identified in this review was a realist evaluation of a single-point coordinated end-of-life care service, 59 which suggested that several mechanisms contributed to success: the presence of coordinated services, the recruitment and development of the workforce, articulation of clear roles and the management of expectations. One approach to evaluate effectiveness of an intervention is to investigate the impact of an intervention on a particular outcome.…”
Section: Infrastructure and Support Systemsmentioning
confidence: 99%